Soluble CD14 concentration in human breast milk and its potential role in child atopic dermatitis: results of the Ulm Birth Cohort Studies - Logan, Chad A.; Brenner, Hermann (Clinical & experimental allergy, 2019)
Background: Soluble CD14 (sCD14) is one of many factors in human breast milk which may influence programming of the immune response in the breastfed child. Although previous studies have mostly found little association between sCD14 concentration in breast milk and atopic outcomes, recent evidence continues to support a role of sCD14 in immune-related disease. Objective: We aimed to clarify whether an association exists between sCD14 concentration in human breast milk (m-sCD14) and child atopic dermatitis (AD) diagnosis by age 3 years within the context of two large birth cohorts. Methods: Data were obtained from the Ulm Birth Cohort Study (UBCS) and the Ulm SPATZ Health Study, methodologically similar birth cohort studies, each consisting of approximately 1000 newborns and their mothers recruited from the general population shortly after delivery in Ulm, Southern Germany, respectively, from 11/2000 to 11/2001 and 04/2012 to 05/2013. sCD14 concentrations were measured by different ELISAs (UBCS: IBL, SPATZ: R&D) in breast milk samples collected at 6 weeks post-delivery in both studies and additionally at 6 months and 1 year in SPATZ. Children's AD diagnosis was assessed using parent and paediatrician reports at 1, 2 and 3 years of age. Results: Complete exposure and outcome data were available for 659 UBCS and 489 SPATZ children. In both cohorts, sCD14 concentration was significantly associated with breastfeeding frequency (P < 0.01). We observed no association between m-sCD14 concentration and child AD diagnosis in either study. Conclusions: Our results do not support an association between sCD14 concentration in mature breast milk and AD among breastfed children.